Synthesis, Characterization, and Antimicrobial Activity of Near-IR Photoactive Functionalized Gold Multibranched Nanoparticles; ChemistryOpen; Vol. 6, iss. 2 - Kalachyova E. Evgeniya; Olshtrem A. A. Anastasiya Andreevna; Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Elashnikov R. Roman; Ulbrich P. Pavel; Rimpelova S. Silvie; Svorcikx V. Vaclav; Lyutakov O. Oleksy (2017, 2017)
Title screen